Persepsi Guru PJOK dan Guru Kelas terhadap Peran PJOK dalam Membangun Karakter Profil Pelajar Pancasila di SD Negeri Kotabaru - Gya Tri Lestari; Nabila Destiana; Amelia Shakilla; Anggi Deviyani; Fauziah Tazkia Nur; Intan Maulida; Obi Robiyalloh; Rahmat Permana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the role of Physical Education, Sports, and Health (PJOK) learning in strengthening students' character values in accordance with the Pancasila Student Profile at the elementary school level in the context of the Merdeka Curriculum. The method used is qualitative with a combination of in-depth interviews with PJOK teachers and class teachers, namely grade 2 and direct observation to the school. The results showed that PJOK lessons have a significant contribution in instilling character values such as cooperation, independence, responsibility, sportsmanship, and respect for others through various physical activities and games. PJOK teachers use persuasive approach strategies and initial assessments to recognize individual student characters so that this learning approach can be adjusted. This is done so that the learning process becomes more effective and relevant to the character needs of students. The main challenges faced in integrating character education are the influence of the environment and the lack of parental participation in shaping student character. Evaluation of student character is done through formative and summative assessments as well as direct observation in students' daily lives in class and during PJOK practice. Collaboration between class teachers and physical education teachers is considered important in harmonizing the character education approach. In general, PJOK learning is considered very effective in shaping student character, especially when supported by extracurricular activities and strengthening the role of families at home.